2018
DOI: 10.1021/acs.biomac.8b00744
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive, Functionalizable Spyrocyclic Polycarbonate: A Versatile Platform for Biocompatible Nanoparticles

Abstract: Polymeric nanoparticles are widely investigated to enhance the selectivity of therapeutics to targeted sites, as well as to increase circulation lifetime and water solubility of poorly soluble drugs. In contrast to the encapsulation of the cargo into the nanostructures, the conjugation directly to the polymer backbone allows better control on the loading and selective triggered release. In this work we report a simple procedure to create biodegradable polycarbonate graft copolymer nanoparticles via a ring open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…These were derived from the reaction of pentaerythritol and 2,4,6-methoxybenzaldehyde or p -methoxybenzaldehyde, respectively, followed by cyclization of the resultant diols by ethyl chloroformate and TEA in THF . Using a similar chemistry, Dove and co-workers reported the synthesis of a norbornene-functionalized spirocyclic carbonate, 9-norbornene-2,4,8,10-tetraoxaspiro­[5,5]­undecan-3-one (NTC) from pentaerythritol and 5-norbornene-2-carboxaldehyde, followed by ring-closure using ethyl chloroformate and TEA …”
Section: Synthetic Methods For the Preparation Of Cyclic Carbonate Mo...mentioning
confidence: 99%
“…These were derived from the reaction of pentaerythritol and 2,4,6-methoxybenzaldehyde or p -methoxybenzaldehyde, respectively, followed by cyclization of the resultant diols by ethyl chloroformate and TEA in THF . Using a similar chemistry, Dove and co-workers reported the synthesis of a norbornene-functionalized spirocyclic carbonate, 9-norbornene-2,4,8,10-tetraoxaspiro­[5,5]­undecan-3-one (NTC) from pentaerythritol and 5-norbornene-2-carboxaldehyde, followed by ring-closure using ethyl chloroformate and TEA …”
Section: Synthetic Methods For the Preparation Of Cyclic Carbonate Mo...mentioning
confidence: 99%
“…As has been previously reported, the acid-catalysed acetal formation between aldehydes and diols offers a facile and efficient route to synthesise monomers and polymers that contain pH sensitive cyclic acetal moieties. 26,27 Acetal-containing diols were generated through the reaction of pentaerythritol with benzaldehyde and norbornene-2-carboxaldehyde under acidic conditions respectively. The utilisation of deionised water as the reaction solvent allowed for the precipitation of the mono-functionalised product from the reaction exclusively ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that the incorporation of norbornene-acetal moieties in an amphiphilic polycarbonate-gpoly(ethylene glycol) system yielded materials which could be easily modified through 'click'-like chemistry and subsequently used as a pH responsive chemotherapeutic delivery system. 26 Herein, we describe the application of previously synthesised 'acetal-diols', (2-phenyl-1,3-dioxane-5,5-diyl)dimethanol (C Ph ) and (2-(norbornene)-1,3-dioxane-5,5-diyl)dimethanol (C Nb ), as extenders in the synthesis of novel TPEUs and assess their structure-property relationship. Furthermore, the postpolymerisation modification of the norbornene-containing TPEUs, as a method of manipulating their physical properties, is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric nanoparticles have emerged as a promising tool in the biomedical field to deliver drugs and imaging agents to the targeted site, enhancing selectivity of therapeutics, increasing circulation lifetime and water solubility of drugs and imaging agents. [ 86–90 ] Targeted delivery technologies are essential to avoid side effects and decrease the administered dose of potentially toxic therapeutics. However, current delivery methods are far from perfect and present substantial challenges that nanomedicine is still facing.…”
Section: Targeting Polymeric Nanoparticles At the Cell Surfacementioning
confidence: 99%